2004
DOI: 10.1109/lcomm.2004.837647
|View full text |Cite
|
Sign up to set email alerts
|

Unified Framework for Linear MIMO Transceivers With Shaping Constraints

Abstract: Abstract-This letter considers optimum linear transceivers for MIMO channels under a general framework based on Schurconcave and Schur-convex cost functions, subject to shaping constraints on the transmit covariance matrix. Such constraints may be useful, for example, to impose spectral masks in cable systems, to control the power transmitted along certain directions in wireless systems, or to limit the dynamic range of the power amplifiers at the different transmit dimensions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(78 citation statements)
references
References 13 publications
1
77
0
Order By: Relevance
“…For large N, it has been observed that, most local minima of the error norm function have small error norms, and therefore low-complexity methods like gradient descent can be used. 8 For very small N = 2, 3 there exist closed-form expressions for Θ u as shown below. 9 From the expressions for the phase angle vector for very small N, and the existence of low-complexity gradient-descent type methods for large N, it is expected that the computational complexity of the proposed CE scheme would not be 8 One method, that we have empirically found to have fast local minima convergence, is to sequentially update one phase angle at a time while keeping the others fixed in such a way that the objective function value e u (Θ)…”
Section: A the Proposed Precoder Map φ(U) = θ Umentioning
confidence: 99%
See 2 more Smart Citations
“…For large N, it has been observed that, most local minima of the error norm function have small error norms, and therefore low-complexity methods like gradient descent can be used. 8 For very small N = 2, 3 there exist closed-form expressions for Θ u as shown below. 9 From the expressions for the phase angle vector for very small N, and the existence of low-complexity gradient-descent type methods for large N, it is expected that the computational complexity of the proposed CE scheme would not be 8 One method, that we have empirically found to have fast local minima convergence, is to sequentially update one phase angle at a time while keeping the others fixed in such a way that the objective function value e u (Θ)…”
Section: A the Proposed Precoder Map φ(U) = θ Umentioning
confidence: 99%
“…For the special case of N = 1 (SISO AWGN), the channel capacity under a CE input constraint has been reported in [7]. However for N > 1, known reported works on per-antenna power constrained communication consider an averageonly or peak-only power constraint [8]- [13]. For the single-user scenario, in [8], the author considers the problem of finding the optimal transmit and receive matrices which maximize the received signal-to-noiseand-interference-ratio (SINR) in a MIMO channel, subject to a per-antenna average power constraint at the TX.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note that the designs considered here are but a subset of the possible implementations. One can derive others using results from [19,20]. The various equivalence relations among different designs under special conditions are discussed in Section 4.4 and summarized in Table 5.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…Since G k,R has been determined previously for inter-pair interference cancellation and is known, the optimal solution {G k,L , F k } for the uplink equivalent problem in (20) and (21) (see [15]) can be used to construct the optimal decoder and precoder {G k = G k,L G k,R , F k } of the k th pair in the uplink framework.…”
Section: Optimalitymentioning
confidence: 99%